Euthanasia and dignity of dying. - Herranz, Gonzalo (Medicina e Morale, 2001)
Inside the theological discussion about the "liberty to die" the following reflection is rising from the part of majority, it is felt that the influence of the so-called (but only so-called…) "liberal Catholicism", especially the thought of liberalists and utilitarians, in the medical field has an ample space. To our appearance it is an inappropriate meaning and a false access to the boundary of liberty that becomes an appeal to construct and to build as much as a "law to die"; but authentically the thought of liberty can't establish a "law to die". It should be a contradiction in terms, because there is a low well more accepted and recognised that is the "law to live"; there is, we think, a law to live qualitatively well, and not only in a biological sense but also anthropological, the supreme act of the human life, that is to die, as an act of life. Also the will (living will) of a patient does not end ultimately in his/her liberty, that which he/she confront it with other wills as occurs in the rest of all human actions. Then, some specifications will be necessary, case for case or for group of cases, act to avoid the possible forms of therapeutic obstinacy where "biological vitality", sometimes artificial and carried out with disproportionate means, is substituted to the properly - ordered life.